2017
DOI: 10.2495/sdp170611
|View full text |Cite
|
Sign up to set email alerts
|

Social Impact of Mobile Learning Tablets on Education and Sustainable Development: Evidence From a Private Nigerian Tertiary Institution

Abstract: The advent of Information and Computer Technology (ICT) has suddenly turned the world into a global village. One of the ICT gadgets that appeared to be instrumental to the growing global socialization is mobile learning tablet. This study focused on ascertaining the social impact of mobile tablets on education and sustainable development. Recently, a private university in Nigeria with a population of over 8000 distributed Samsung tablet to all students. Using the clustered sampling technique, 220 students part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Territorial and environmental problems demand, now more than ever, and particularly in our country, where the situation is dramatic, the constant presence of the geologist in all social, cultural, economic and territorial contexts. Following the philosophy of the project, one can compare the geologist to the medical doctor [65], that is, we must leave the offices, laboratories, and teaching halls and go and talk to the people [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Territorial and environmental problems demand, now more than ever, and particularly in our country, where the situation is dramatic, the constant presence of the geologist in all social, cultural, economic and territorial contexts. Following the philosophy of the project, one can compare the geologist to the medical doctor [65], that is, we must leave the offices, laboratories, and teaching halls and go and talk to the people [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Este problema también es resaltado por los docentes y los padres de familia, a quienes les preocupa el entorpecimiento del proceso de enseñanza-aprendizaje por el uso incorrecto de estas herramientas. Para que el potencial de las tabletas se realice plenamente, los estudiantes interesados deben ejercer más autocontrol y disciplina para evitar perder tiempo realizando actividades que no estén relacionadas con los objetivos de la clase, del mismo modo, la administración escolar y los padres deben desarrollar dispositivos de control más automatizados para evitar que los jóvenes hagan uso desmesurado de esta herramienta (Odukoya, Ebenezer, y Okunlola, 2017).…”
Section: Uso De Dispositivos Móviles En Educación Superiorunclassified
“…Although, the works of (Odukoya et al, 2017a;Odukoya et al, 2017b) have shown positive impacts of mobile phone and tablets among students, as it could enable students to easily communicate with their parents, friends and relations outside the university but the policy does not prevent students" access to mobile phone; it only provides opportunities to make calls in designated call centres on campus. Apart from that, the policy permits each student to own a tablet which can be used for effective communication through the WhatsApp application.…”
Section: Policies Of the Institution Under Study Fundamental Human Rmentioning
confidence: 99%